PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR KOMPETENSI DASAR PEMBENTUKAN LOGAM DENGAN BLENDED LEARNING BERBANTUAN MEDIA SOSIAL SCHOOLOGY DI KELAS X TKRD SMK NEGERI 2 SURAKARTA - Widiyanto, Teguh (Jurnal Nosel, 2015)
The purpose of this research is to improve learning activity and learning achievement of metal forming basic competence at the TKRD first grade of SMK Negeri 2 Surakarta using blended learning supported by schoology social media. This research is classroom action research. This research is done two cycles, which each cycles consists of planning, acting, observing and reflecting. The subjetcs of this research are 32 student of TKRD first grade of SMK Negeri 2 Surakarta. The data source is from teacher and students. The techniques of collecting data are observation, test, documentation, and questionnaire. This research uses content and contruct validity. This research uses comparative analysis technique and statistic deskriptive. The result show that (1) the use of blended learning supported by schoology social media could improve learning activity. It is show by the percentage of students before the action is 30,81%. After the action is done, the percentage becomes 63% in the first cycle and improves to be 76,9% in the second cycle. (2) the use of blended learning supported by schoology social media could improve the learning achievement. It is show by the persentage of learning achievement completeness before the action is 43,7%. After the action, the persentage in of learning achievement completeness is 53,12% and becomes 84,38% in the second cycle. The conclusion of this research is the using of blended learning supported by schoology social media could improve learning activity and learning achievement of metal forming basic competence at the TKRD first grade of SMK Negeri 2 Surakarta.